2021
DOI: 10.1017/s002221512100414x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hearing loss in neonates admitted to neonatal intensive care units

Abstract: Objective This study aimed to research risk factors of hearing loss among neonates in the neonatal intensive care unit. Method Hearing screening tests were performed on 572 neonates in the neonatal intensive care unit. Those who failed screening tests were referred for diagnostic tests. Results The pass rates for automated auditory brainstem response, distortion product otoacoustic emission and acoustic impedance tests at first hearing screening were 69.93 per cent, 70.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Literature has reported that clinical information such as premature birth [ 9 , 10 ] and brain structural MRI assessment such as white matter lesions [ 11 , 12 ] being related to hearing loss in newborns. Additional factors such as age at CI surgery [ [13] , [14] , [15] ], preoperative speech rehabilitation training [ 16 ], the width of bony cochlear nerve canal [ 17 , 18 ] and the diameter of internal auditory canal [ 19 ] have been shown to be related to the rehabilitation outcome after CI surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Literature has reported that clinical information such as premature birth [ 9 , 10 ] and brain structural MRI assessment such as white matter lesions [ 11 , 12 ] being related to hearing loss in newborns. Additional factors such as age at CI surgery [ [13] , [14] , [15] ], preoperative speech rehabilitation training [ 16 ], the width of bony cochlear nerve canal [ 17 , 18 ] and the diameter of internal auditory canal [ 19 ] have been shown to be related to the rehabilitation outcome after CI surgery.…”
Section: Introductionmentioning
confidence: 99%